Game, toy, and elderly. A necessary approach from a systematic review - Leonardo Andrés Aguirre-Cardona; Luz Elena Mendoza-Espinel (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The experience, study, enjoyment, and even the social projection of the game and the toy, permeates the different stages of life and from the perspective of the elderly adult deserves special attention, even more so when this is a population segment that is in constant growth and constitutes a scenario of reflections and analysis from a position of Physical Education, Recreation and Sports, which allows us to think that, although games and toys are widely approached since childhood, this dialogue is not very clear between game, toy and elderly. The study aims to identify the investigative approaches around games, toys, and the elderly via a literature review. The studies identified in the major collections of the Scopus, Web of Science, and PubMed databases were used, with 72 articles whose analysis started from reviewing the aspects of title, objective, design, sample, and results. The review shows that games and toys as a strategy for health promotion and disease prevention in the elderly emerge as a possible trend that contributes to this area of study and intervention and contributes to body maintenance, cognitive and social in the elderly.